An Overview of Artificial Intelligence, Ethic and Neuromodulation - Fuentes-Penna, Alejandro; Barrera Cámara, Ricardo A.; Gómez Cárdenas, Raúl; Hernández González, Óscar Daniel; Castro Rascón, Aristeo (International Journal of Combinatorial Optimization Problems and Informatics, 2026)
Based on advances in computing and devices as an extension of the human body, new technologies focused on neuromodulation and with the help of artificial intelligence, can generate lucid dreams and even improve concentration. With noise cancellation through devices such as smart hearing aids or with the generation of devices that detect and modify brain waves, the human body has been empowered towards mental conditions and, in a sense, towards improving the quality of life through sleep. of life through sleep. However, we would be at a point where the ethics and philosophy of technology ethics and the philosophy of technology converge to identify the use of such devices to improve human devices to improve human conditions without overstepping the legal and ethical realm in their use. Smart citations: https://scite.ai/reports/10.61467/2007.1558.2026.v17i2.1135 Dimensions. Open Alex.